Pengaruh Job Description dan Kepuasan Karyawan terhadap Kinerja Karyawan (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2025)
The purpose of this research is to determine the effect of job description and employee satisfaction on employee performance. This research was conducted at UD. Budi Jaya in Denpasar with a population of 32 employees. This research uses census techniques so that all members of the population are involved as research subjects. Primary data collection was carried out using a questionnaire. Hypothesis testing is carried out using multiple linear regression. Based on the results of the analysis, it can be concluded that: 1) job descriptions have a positive and significant effect on employee performance, 2) employee satisfaction has a positive and significant effect on employee performance, 3) job descriptions and employee satisfaction have a positive and significant effect on employee performance. In improving employee performance, UD. Budi Jaya in Denpasar is expected to be able to provide regular training which is useful for improving employee skills so that employees can minimize errors at work, carry out position promotion programs based on considerations of experience, ability and related requirements and leaders are expected to be able to apply the style transformational or charismatic leadership